Evaluation of the hypothalamus-pituitary axis response to exogenous GnRH, estradiol benzoate, And LH during the postpartum period in Nellore cows - Pinheiro, Vinícius G.; Cury, José Renato L. M.; Satrapa, Rafael A.; Trinca, Luzia A.; Loureiro, Bárbara; Barros, Ciro M. (Elsevier, 2013)
The objective was to evaluate when the LH reserve was re-established in postpartum Nellore (Bos indicus) cows by evaluating the response of the hypothalamic-pituitary axis responsiveness to exogenous GnRH or estradiol benzoate (EB). Additionally, we tested the influence of dietary supplementation (SUPL) and calf removal (CR) on the duration of postpartum anestrus. Ninety multiparous lactating Nellore cows were randomly assigned to eight groups. The EB and GnRH groups received 1.0 mg EB (N = 7), and 50 μg lecireline (N = 16), respectively. Additional cows were given the same hormones, and subjected to either nutritional supplementation (EB-SUPL, N = 9; GnRH-SUPL, N = 16), or calf removal at 72 hours after calving (EB-CR, N = 4; GnRH-CR, N = 13). The remaining two groups were the LH (12.5 mg, N = 14) and control groups (saline, N = 11). Hormones were administered weekly from 7 (±5) days postpartum to first ovulation (detection of a CL during a weekly ultrasonographic examination). Blood samples were collected just before and 2 hours (GnRH, LH, and control groups) or 18 hours (EB groups) after hormone or saline (control) administration. Ovulation occurred as early as 15 days postpartum in the GnRH group. The mean ± SEM intervals (days) from calving to first ovulation were EB, 87.7 ± 4.2; EB-CR, 20.3 ± 1.2; EB-SUPL, 60.3 ± 3.2; GnRH, 40.4 ± 2.1; GnRH-CR, 21.0 ± 1.1; GnRH-SUPL, 26.4 ± 1.1; LH, 35.6 ± 1.1; and control, 60.9 ± 2.1. We concluded that there was sufficient LH in the pituitary gland (of Nellore cows) from the second week postpartum to induce ovulation in response to exogenous GnRH. Additionally, calf removal and nutritional supplementation reduced, by 2 to 4 weeks, the interval from calving to an LH increase and ovulation induced by GnRH or EB. © 2013.
Keywords: Anestrus; Bos indicus; GnRH; LH; Nellore; Postpartum; drug derivative; estradiol; estradiol 3-benzoate; estradiol benzoate; gonadorelin; luteinizing hormone; animal; animal food; body weight; cattle; controlled clinical trial; controlled study; drug effect; female; histology; hypothalamus hypophysis system; metabolism; ovulation; physiology; puerperium; randomized controlled trial; Animal Feed; Animals; Body Weight; Cattle; Estradiol; Female; Gonadotropin-Releasing Hormone; Hypothalamo-Hypophyseal System; Luteinizing Hormone; Ovulation; Postpartum Period